Towards Using Semantic Methods in Evaluation of Internet-Based Information Trustworthiness - Kajfosz, Kinga (Advanced Information Technologies for Management – AITM 2009, 2009)
One of the serious difficulties we meet using the Internet is the trustworthiness of found information. With regard to this there is a request for a method of Internet-based information evaluation especially for software agents. In the paper the author described an ontology-oriented approach of information trustworthiness evaluation. The author showed the ontology as a semantic method of knowledge representation. Afterwards the usefulness of the ontology-oriented approach in creation of Internet-based information evaluation systems was proven.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 85, s. 126-132